2016
DOI: 10.1103/physrevc.93.034303
|View full text |Cite
|
Sign up to set email alerts
|

First observation of low-energyγ-ray enhancement in the rare-earth region

Abstract: The γ-ray strength function and level density in the quasi-continuum of 151,153 Sm have been measured using BGO shielded Ge clover detectors of the STARLiTeR system. The Compton shields allow for an extraction of the γ strength down to unprecedentedly low γ energies of ≈ 500 keV. For the first time an enhanced lowenergy γ-ray strength has been observed in the rare-earth region. In addition, for the first time both the upbend and the well known scissors resonance have been observed simultaneously for the same … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
56
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 56 publications
12
56
3
Order By: Relevance
“…(19). For deformed nuclei, the GDR strength is defined as the sum of two components, each of them given by Eq.…”
Section: B γ -Strength Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…(19). For deformed nuclei, the GDR strength is defined as the sum of two components, each of them given by Eq.…”
Section: B γ -Strength Functionmentioning
confidence: 99%
“…For deformed nuclei, the GDR strength is defined as the sum of two components, each of them given by Eq. (19). Therefore, the GDR parameters that needed to be determined were T f , E E1,i , E1,i , and σ E1,i , where i = 1,2 indicates whether the oscillation is parallel or perpendicular to the main symmetry axis.…”
Section: B γ -Strength Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade things have become more complicated, since measurements of the γSF [10,[14][15][16][17][18][19][20][21][22][23][24][25][26] have revealed a newly observed minimum around E γ ≃ 2 − 4 MeV, so besides the high E γ enhancement, there is also a low E γ enhancement. The first attempts to understand the low-E γ enhancement [14,15,17] used the KMF model to describe the GDR; the contribution of the giant magnetic dipole resonance to the total γSF is fitted by a Lorentzian, similarly to the E2 resonance, while the low-E γ region is described by a separate term that has a power-law parametrization.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in rare earth nuclei have shown [9,10] that bumps in the E γ ≈ 3 MeV region are of M1 character. Actually, the M1 transitions seem to play an active role in the γSF being described also by a Lorentz line [11] based on the existence of a resonance that originates from spin-flip excitations in the nucleus [12,13].…”
Section: Introductionmentioning
confidence: 99%